Climate Innovation Liberal Capitalism and Climate Change - Harrison, N.; Mikler, J.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
A comprehensive examination of the inability of liberal capitalism to generate the technological innovations necessary to prevent dangerous climate change. The case is made for the need for institutional evolution to drive the climate innovation, and the potential for climate innovation in an increasingly economically interconnected world.
Keywords: Environmental policy; Environmental geography; Political science; Political economy; Globalization; Environmental economics; Environmental Politics; Environmental Geography; Political Science; International Political Economy; Globalization; Environmental Economics